1994
DOI: 10.1007/bf00414860
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characteristics of soybean-fortified gari

Abstract: Two cassava cultivars were fermented for 3 days with the incorporation of soybean residue or full-fat flour at 25% (w/w) to produce gari. Unfortified gari was superior in taste (P<0.05) to the soybean-fortified gari, though consumers still accepted the latter. Fortified samples from two of the three procedures used, in which soybean was added at different stages of the fermentation, were rated similarly (P>0.05). The water activity of soybean-fortified gari was <0.7, the swelling capacity was 2.5 to 3.3, pH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 4 publications
3
23
0
Order By: Relevance
“…This observation is in agreement with the reports of previous studies carried out by Sanni and Sobamiwa (1994) and Kolapo and Sanni (2005). The population of yeasts increased during storage of the ogi.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This observation is in agreement with the reports of previous studies carried out by Sanni and Sobamiwa (1994) and Kolapo and Sanni (2005). The population of yeasts increased during storage of the ogi.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have indicated that loss in nutrient during the various stages of ogi production might be compensated by combining two different cereals (Banigo and Muller, 1972); and incorporation of soybeans (Adeleke and Oyewole., 2010). Kolapo and Sanni (2005) and Sanni and Sobamiwa (1994) also reported improvement in protein content of tapioca and gari respectively due to fortification with soybeans. There was a significant difference in sensory property of ogi samples fortified with soybeans and unfortified samples.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations